2012
DOI: 10.1038/ejhg.2012.179
|View full text |Cite
|
Sign up to set email alerts
|

Intentions to receive individual results from whole-genome sequencing among participants in the ClinSeq study

Abstract: Genome sequencing has been rapidly integrated into clinical research and is currently marketed to health-care practitioners and consumers alike. The volume of sequencing data generated for a single individual and the wide range of findings from wholegenome sequencing raise critical questions about the return of results and their potential value for end-users. We conducted a mixed-methods study of 311 sequential participants in the NIH ClinSeq study to assess general preferences and specific attitudes toward le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
202
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(232 citation statements)
references
References 26 publications
29
202
1
Order By: Relevance
“…The authors also found that their results reflected the ability of the participants to discriminate between different types of genetic results. 19 Shahmirzadi et al 20 conducted a retrospective study on the patients' decisions to learn IFs when undergoing clinical WES. In this study, the options for IFs where divided into carrier status of recessive disorders, predisposition to late-onset diseases, predisposition to increased cancer risk and early-onset diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that their results reflected the ability of the participants to discriminate between different types of genetic results. 19 Shahmirzadi et al 20 conducted a retrospective study on the patients' decisions to learn IFs when undergoing clinical WES. In this study, the options for IFs where divided into carrier status of recessive disorders, predisposition to late-onset diseases, predisposition to increased cancer risk and early-onset diseases.…”
Section: Discussionmentioning
confidence: 99%
“…17 In addition, issues of access and equity have started to be raised in the conceptual literature, 24 and there is some empirical evidence of consumer concern about access to relevant tests. 17,21 In addition, emerging literature attends to the identification of genetic risk information using next-generation sequencing technologies and highlights expectations related to research participation and preferences for results, 25 including incidental results. Yet, although research exploring patient experiences with testing for inherited health risks is extensive, 26,27 research on the effects of receiving unexpected or uncertain genetic information is less developed.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic information that is of clinical relevance, even when not related to the reason for testing, and that will affect the patient, their relatives, and/or their offspring should always be disclosed for preventable or treatable diseases like Lynch syndrome, cancer-related genes such as breast cancer 1, early onset (BRCA1) 5 and breast cancer 2, early onset (BRCA2), and carrier status. In one study, patients were most interested in receiving WGS results for a preventable or treatable disease and determining carrier status (36 ). Information about risks for future diseases that are nonpreventable and/or untreatable like Huntington disease and carrying the APOE4 variant of the apolipoprotein E (APOE) gene (associated with Alzheimer disease) should be disclosed only with prior patient consent.…”
Section: Interpretative and Ethical Issuesmentioning
confidence: 99%